2019
DOI: 10.1111/acel.12892
|View full text |Cite
|
Sign up to set email alerts
|

The mir‐465 family is upregulated with age and attenuates growth hormone signaling in mouse liver

Abstract: We analyzed the small RNA transcriptome from 5‐month‐old, 24‐month‐old, and 36‐month‐old mouse liver and found 56 miRNAs that changed their expression profile with age. Among these is a cluster of 18 miRNAs that are upregulated between 50‐ and 1,000‐fold at 24 and 36 months of age. This cluster is located in a 60‐kb region of the X‐chromosome that is devoid of other coding sequences and is part of a lamin‐associated domain. Potential targets of the miRNAs in the cluster suggest they may regulate several pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Although synergistic actions of GH and insulin on STAT5 remain unclear, lower activation of STAT5 in a knockout of insulin receptor has been reported [ 46 ]. Moreover, transfection of a liver cell line with mir-465 mimics, which may affect genes of PI3K-Akt pathway, reduces STAT5 phosphorylation upon GH stimulation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although synergistic actions of GH and insulin on STAT5 remain unclear, lower activation of STAT5 in a knockout of insulin receptor has been reported [ 46 ]. Moreover, transfection of a liver cell line with mir-465 mimics, which may affect genes of PI3K-Akt pathway, reduces STAT5 phosphorylation upon GH stimulation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms surrounding the natural reduction in GH and IGF-1 are not clearly understood. Recently, it was shown that the mir-465 family of miRNAs is upregulated with age in mouse liver and can directly influence GH signaling by targeting the GHR mRNA [4]. The mir-465 family consists of five genes located on the X-chromosome: one copy of mir-465a, and two copies each of mir-465b and mir-465c.…”
mentioning
confidence: 99%
“…The mir-465 family is part of a cluster of 18 miRNAs that are normally tightly repressed in liver. However, all 18 miRNAs in this cluster are upregulated with age [4]. This cluster is located in a highly heterochromatic region of the X-chromosome that is rich in repetitive elements and devoid of other coding sequences, consistent with constitutive heterochromatin.…”
mentioning
confidence: 99%
See 2 more Smart Citations